Hodgkin lymphoma in patient with primary immunodeficiency: clinical features and treatment approaches - K. I. Utesheva; E. S. Belyaeva; T. T. Valiev; A. A. Odzharova (Онкогематология, 2022)
Primary immunodeficiencies (PID) are genetically determined irreversible disorders of structure and/or functions of the immune system's cellular and humoral components, accompanied by frequent infectious diseases and contributing to the development of malignant neoplasms. Lymphomas are the most frequent oncological disease in PID patients: non-Hodgkin's lymphomas occur in 60 % of malignant neoplasms cases, Hodgkin lymphoma - in 20 %, leukemias - in 10 %, solid tumors - in 10 %. The risk of malignant lymphoproliferative diseases in PID patients amounts to 4-25 %, with the overall incidence of cancer 100-200 times higher than in immunocompetent population. Results of malignant neoplasms treatment in children with PID remain unsatisfactory due to the high rate of relapsed, refractory disease and anticancer therapy complications.This paper presents a clinical case of Hodgkin lymphoma with atypical localization in a female PID patient. peculiarities of this case are eye socket soft tissue involvement, slow response to therapy, and a high rate of infectious complications.